EFFECT OF CARBOHYDRATE (STARCH) LEVEL IN PURIFIED DIETS ON THE GROWTH OF PENAEUS INDICUS - Ali, Syed Ahmed (Indian Journal of Fisheries, 2011)
Four purified diets were formulated using casein, gelatin, starch, fish oil, groundnut oil, vitainins, minerals and cellulose. The carbohydrate in the dietsi was increased from 10 to 40% Tay varying the starch content to study the effect of dietary carbohydrate level on the growth, survival and food conversion of the prawn Penaeus indicus The protein and the lipid contents were kept constant in all the diets. Feeding experiments conducted in the laboratory on the juvenile P. indicus indicated that the growth of prawn increased with increase in the dietary carbohydrate level from 10 to 40% (P <; 0.01). The food-conversion efliciency and the rate of Sfurvival improved with the increase of carbohydrate level in the diet. The growth also increased with the increase of carbohydrate calorie ratio, while it was better with lower protein carbohydrate ratio of the diets.